Development of an agent based modelling and simulation tool for anticipatory change planning for cellular transport systems - Karakaya, Elif (Nobel, 2015)
Die vorliegende Dissertation adressiert die Zellulare Fördertechnik (ZFT) als ein spezielles Intralogistiksystem, um ein integriertes Simulationssystem zur systematischen Antizipation von Veränderungstreibern sowie Auswahl von Optimierungsmaßnahmen zu entwickeln. Um dies zu erreichen, wird zuerst die ZFT mitsamt ihrer Konstituenten definiert und beschrieben. Darauf aufbauend wird die Antizipative Veränderungsplanung (AVP) als ein anwendungsorientierter systematischer Experimentieransatz entwickelt, welche insbesondere für die ZFT aufgrund ihrer Flexibilität und Anpassungsfähigkeit von Bedeutung ist. Hiermit kann jeder einzelne Veränderungstreiber, der einen Einfluss auf die ZFT hat, getestet werden, sowie die Bedingungen eines Lagers bei Anwendung einzelner Maßnahmen bewertet werden. Abschließend wird die ZFT anhand eines Multiagenten-Systems simuliert. Auf Basis üblicher und extremer Fallstudien wird das Verhalten der ZFT analysiert und effektive Maßnahmen werden getestet und bewertet. Die Dissertation belegt die Anwendbarkeit der agentenbasierten Simulation für die antizipative Veränderungsplanung der Zellularen Fördertechnik.

The dissertation focuses on the specific intralogistics system called Cellular Transport System (CTS) to develop an integrated simulation tool in order to systematically anticipate change drivers and select optimization measures for CTS. To achieve this, firstly, CTS and it constituents are defined and introduced. Secondly, the Anticipatory Change Planning (ACP) as an applicable systematic experimentation approach is developed. That is especially required for CTS because of its flexibility and adaptability. Thus, each significant change driver which has influence on the CTS can be tested, and the conditions of the warehouse, with or without measured effects can be assessed under favour of the holistic ACP framework. Lastly, the CTS is simulated based on the agent-based simulation methodology within the scope of this research. Based on several usual and extreme case studies the behaviour of CTS is analyzed and effective adaptation measures are tested and evaluated. The dissertation proves the applicability and usefulness of agent-based simulation for the anticipatory change planning of Cellular Transport Systems.
Keywords: Agent based simulation; Cellular transport system; 620; 670; Simulation; Transportsystem; Intralogistik; Fördertechnik